EFEK NILAI KERJA, OTONOMI, DAN WORK SETTING TERHADAP KEPEMIMPINAN DAN PERILAKU ORGANISASI PADA INDUSTRI JASA PERHOTELAN - Dea Prasetyawati; Andreas W. Gunawan Putra (Jurnal Manajemen dan Pemasaran Jasa, 2010)
Hotel, when business and leisure blend in harmony, as one of service industry sector which has a perishable product as main product, based on their employees interaction.The service activities were produce by the employees, to keep it sustainable theemployees should be firm with their company. The antecedents of Organizational Citizenship Behaviors will appear by their answer to our question to prove about the effect of work value, autonomy and work setting on Leadership, and of course to OCBitself. This could drive a firm and comfort working condition to generate a greatservice quality.This research was done in a hotel in West Jakarta. The purpose of this study was to analyze the effect of work value, autonomy and work setting on leadership and organizational behaviors.Sample was collected from 172 employees, as our respondents. The collected data was analyzed with SEM analysis, and the questionnaire was adopted from Wright (2008).The findings suggest that work value and autonomy have significant effect on leadership. Besides, work setting has no effect on leaderships and leadership has no effect on organizational citizenship behaviors.Keywords: Work Value,Autonomy, Work Setting, Leadership, OCB, Hotel Industry